Malignant Granular Cell Tumor of the Abdominal Wall Mimicking Desmoid Tumor: A Case Report with CT Imaging Findings and Literature Review - Yoon, Jehong; Ahn, Sung Eun; Lee, Dong Ho; Park, Seong Jin; Moon, Sung Kyoung; Lim, Joo Won (Journal of the Korean Society of Radiology, 2016)
Granular cell tumors (GCTs) are extremely rare mesenchymal neoplasms of Schwann cell origin. Malignant GCTs (MGCTs) comprise 0.5–2% of all GCTs. In the present report, we describe a case of a 66-year-old man with MGCT of the abdominal wall. The patient visited our hospital due to a recently growing palpable soft tissue mass in the abdominal wall. Computed tomography scan revealed a 4.3 × 4.1 × 2.9 cm sized mass arising from the left abdominal wall, which was contemplated as a desmoid tumor before surgical excision. Histopathological examination confirmed MGCT.